Establishment of in vitro regeneration and transformation protocol in tomato (Lycopersicon esculentum Miller)" - Chowdhury, Jebunnesa (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2009